Embracing consumer ambivalence in the luxury shopping experience. Issue 5 (25th February 2021) - Prestini, Stefano; Sebastiani, Roberta
Abstract: Emotions, feelings, attitudes, and beliefs play a pivotal role in consumer decision‐making. The literature shows that psychological concepts with opposing valence coexist in people's shopping experience. This consumer ambivalence is relevant in hedonic contexts, where cognitive and affective elements play a central role in consumer outcomes (e.g., satisfaction, loyalty, and patronage). However, there is a paucity of consumer ambivalence literature focused on hedonic retail settings; thus, this study focuses on consumer ambivalence in luxury shopping experiences. Using a multi‐method approach, the study investigated luxury shoppers' psychological concepts, both positive and negative, in order to better understand consumer ambivalence and its impact on consumer outcomes. Thus, this paper makes two main contributions. First, it revealed three types of consumer ambivalence: awe and pride; uncertainty and contentment; guilt and pleasure. Second, the combination of negative and positive cognitive and affective elements in the luxury shopping experience positively impacted consumer outcomes and led to specific shopping behaviors. On these bases, luxury brands should leverage consumer ambivalences that are embedded in and signify the overall shopping experience.